Pengaruh Kecukupan Modal, Likuiditas dan Profitabilitas terhadap Kinerja Keuangan pada Perusahaan BUMN yang Terdaftar di IDX-MES BUMN 17 - Wati, Sintia; Habibi, Azwar (Budgeting: Jurnal Akuntansi Syariah, 2025)
In this study, Financial Performance is calculated using Return On Asset (ROA). The source is obtained from secondary data in the form of annual data that can be obtained from the BUMN website. The population used is the financial reports of BUMN companies listed on IDX-MES BUMN 17 with a sample in the form of 42 financial reports. The purpose of this investigation is to test the result of capital adequacy, The impact of profitability and liquidity on financial performance in BUMN companies listed on IDX-MES BUMN 17. The results of the partial t-test indicate that Capital Adequacy, Liquidity, and Profitability have a significant effect on financial performance. Meanwhile, the F-test's findings analysis indicate that capital adequacy, liquidity and profitability have a simultaneous effect on Financial Performance.